Self-control strategy as a cognitive-behavioral treatment method in reducing depression among the elderly in the nursing home - adda, zohra (Journal of Social Sciences and Humanities, 2025)
The study aims to identify the effectiveness of the therapeutic program of behavioral cognitive to reduce depression in the elderly who are the role of care by applying cognitive therapeutic strategies behavioral through self - control over is composed of 15 elderly sample have a state of depression between the simple and very .the results between the measurement pre and post a measure of depression and self-control The presence of functional differences, and this indicates the effectiveness of the therapeutic program in the alleviation of depression among elderly people in the care home.